An experimental approach on energy dissipation of bolted joints using a modified oscillator device. (September 2022) - Li, Yikun; Hao, Zhiming; Du, Qiang; Xing, Minglu; Dou, Linlong; Li, Yifei
A modified and simplified oscillator device is designed and manufactured to investigate the effects of contact roughness and bolt arrangements on energy dissipation caused by joint damping. Three types of surface roughness and five different bolt arrangements are discussed. Identification of Iwan model based on experimental data is carried out. It is indicated that rough surface dissipates more energy than smooth one. Specimens with more bolts dissipate relatively more energy. When bolt number is consistent, the series type dissipates more energy than the parallel type. Experimental data show a good stability and accuracy of the proposed oscillator device. The identified Iwan model provides a good conformity with the reconstructed hysteresis loop. The four-parameter Iwan model can well describe the damping property of joints with different surface roughness and bolt arrangements.